PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE PERTANYAAN PENILAIAN TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMP NEGERI 13 PADANG TAHUN PELAJARAN 2013/2014 - Fitri, Lisfia - (STKIP PGRI Sumbar, 2014)
This study was motivated by an understanding of mathematical concept students are still low and the students do not understand about the subject matter because it does not want to learn at home , resulting in a low student math learning outcomes. This type of research is experimental research design randomized trials on the subject . The population of this study is the eighth grade students of SMP Negeri 13 Padang and the sample was grade VIII.6 VIII.9 experimental class and control class . The instrument used in this study is the essay test . Data were analyzed using t-test . Based on the analysis of data obtained by the average student learning outcomes experimental class higher than the control class. Thus , it can be concluded that the ability of understanding mathematical concepts students use the Question Type Active strategy assessment better than conventional learning at Junior High School eighth grade 13 Padang .